The function f is such that f(x) = x^2 – 2x + 3
Solve f(x) = 27
(The bottom question in the photo)
![The function f is such that fx x2 2x 3 Solve fx 27 The bottom question in the photo class=](https://us-static.z-dn.net/files/dbe/829bbb9e29ec2e55c44bb0e3efc3b4fb.png)
Answer:
x = - 4, x = 6
Step-by-step explanation:
Given
f(x) = x² - 2x + 3 and f(x) = 27, then equating the 2 gives
x² - 2x + 3 = 27 ( subtract 27 from both sides )
x² - 2x - 24 = 0 ← in standard form
Consider the factors of the constant term (- 24) which sum to give the coefficient of the x- term (- 2)
The factors are - 6 and + 4, since
- 6 × 4 = - 24 and - 6 + 4 = - 2, thus
(x - 6)(x + 4) = 0
Equate each factor to zero and solve for x
x - 6 = 0 ⇒ x = 6
x + 4 = 0 ⇒ x = - 4
f(x)= 27
x^2 -2x+3=27
×^-2x+3-27=0
x^2x-24=0
(x-6)(x-4)=0
x-6=0 or ×-4=0
×=6or ×=4